Examining the challenges experienced by trainee teachers in use of transitional devices to achieve cohesion in writing in St. Francis and St. Teresa’s Colleges of Education, Ghana - Giddi, Ebenezer; Kpeglo, Samuel Bruce; Fosu, Juliana (Research Journal in Advanced Social Sciences, 2022)
Transitional devices are crucial in achieving cohesion inwritten communication. This study was conducted to investigate the challenges trainee teachers experience with using these transitional devices to achieve cohesion in writing in St. Francis and St. Teresa’s Colleges of Education. The study used thematic analyses to examine data collected from two hundred and forty trainee teachers and eleven tutors from the two colleges using essays and semi-structured interviews. Sampling was done using simple random sampling and purposive technique to select the trainees and census sampling for the lecturers. The findings showed that the trainee teachers have problems with the use of transitional devices because they misplace the transitions, omit the transitions in certain instances, use nonstandard forms of the devices, wrongly spell the devices, and use them incorrectly in terms of grammar.